Peri-operative fluid management during neurosurgical procedures - Bersot, Carlos Darcy; Linhares, Rafael; Barbosa, Carolina Araujo; Pereira, Jose Eduardo (Nepal Journal of Neuroscience, 2021)
The management of fluids and electrolytes in neurosurgical patients aims to reduce the risk of cerebral oedema, reduce ICP and at the same time maintain haemodynamic stability and cerebral perfusion. Neurosurgical patients commonly receive diuretics (mannitol and furosemide), developing complications such as bleeding and diabetes insipidus. These patients may require large volumes of intravenous fluids and even blood transfusions for volume resuscitation, treatment of cerebral vasospasm, correction of preoperative dehydration or maintenance of haemodynamic stability. Goal-oriented therapy is recommended in neurological patients, with the aim of maintaining circulating volume and tolerating the changes induced by anaesthesia (vasodilation and myocardial depression).